O processo de escolarização na província da Parahyba do Norte: aulas de primeira letras (1834-1849) - Silva, Adriano Soares da (2013)
In this dissertation we analyze the schooling process in the Province of North Parahyba between 1834 to 1849, focusing mainly on teaching in primary education. This period was marked by the diversity of laws designed for the instruction of society as well as the debates on the need to educate the less affluent population. The object of our research is the primary education classes, therefore, we work with the Laws and Regulations of Education in the Province of North Parahyba, the official letters and correspondences exchanged between teachers and the provincial authorities, and finally, the reports of the President of the Province. We studied the importance of organization of public education, the need to create public primary education classes and / or schools; the existing mutual teaching and simultaneous methods and the process of hiring and training teachers. We analyze teachers instruction in the process of institutionalization of the primary education school, their conduct, expertise and obligations to fulfill the requirements of the Provincial Government. We inventoried the obligations of students, the holidays and class schedule, and the physical punishment as constructive elements of, the organization of classes of elementary public education.